Distributed Leadership The Dynamics of Balancing Leadership with Followership (Palgrave Studies in Leadership and Followership,, 2018)
Addressing the area of shared leadership, also known as collective or distributed leadership, this edited book embraces the underlying idea that leadership is a dynamic process that intersects closely with followership. While some authors present rigorously researched qualitative and quantitative case studies that investigate the dynamics of followership in distributive leadership in terms of collective decision-making, leadership identity, roles and demographic composition of groups in a variety of settings, other authors take a critical look at distributed leadership models by viewing them through the lens of nature and ecosystems as well as human development processes. The chapters aim to inspire readers to challenge the current definition of leadership and explore more inclusive and holistic paradigms. Distributed Leadership provides a comprehensive and constructive contribution to the field of leadership and will be an essential read for academics and scholar-practitioners interested in business management.